2014
DOI: 10.1210/en.2014-1271
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Intolerance in Aging Male IGFBP-3 Transgenic Mice: Differential Effects of Human IGFBP-3 and Its Mutant IGFBP-3 Devoid of IGF Binding Ability

Abstract: We have reported a reduction of insulin secretion and glucose intolerance in young mice overexpressing human IGFBP-3 (phosphoglycerate kinase [PGK]BP3) or its mutant Gly56/Gly80/Gly81-IGFBP-3 (PGKmutBP3) under the PGK promoter. Here, we investigated changes in glucose and lipid homeostasis with age in PGKBP3 and PGKmutBP3 mice compared with wild-type mice. Body weight, glucose tolerance, insulin tolerance, visceral fat, interscapular brown adipose tissue (BAT), serum lipids, and pancreas histology were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 55 publications
(82 reference statements)
1
16
0
Order By: Relevance
“…The effects of IGFBP-3 on brown adipocyte growth and differentiation have not been studied before. However, we have recently observed a similar reduction of brown adipose genes in aging PGKmutBP3 mice (14). Our study, in some respects, also agrees with the reports that IGFBP-3 stimulates growth of some cell types.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The effects of IGFBP-3 on brown adipocyte growth and differentiation have not been studied before. However, we have recently observed a similar reduction of brown adipose genes in aging PGKmutBP3 mice (14). Our study, in some respects, also agrees with the reports that IGFBP-3 stimulates growth of some cell types.…”
Section: Discussionsupporting
confidence: 92%
“…Our group has previously reported that the expression of endogenous mouse IGFBP-3 is not affected by hIGFBP-3 overexpression (15). Because of differences in IGF binding between hIGFBP-3 and its mutant, the quenching of IGF-I produced in brown preadipocytes was likely greater in PGKBP3 than in wild-type cells, and smallest in PGKmutBP3 cells (14,15). Therefore, free IGF-I level was likely greatest in PGKmutBP3 cells, smallest in PGKBP3 cells, and intermediate in wild-type cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One sample each from WT and Chd8 +/del5 was removed from Q-fraction analysis due to difficulties in selecting the VZ. All immunolabeling was carried out on slide-mounted cryosections (18 μm) following standard protocols and using primary antibodies directed against Pax6 42 (PRB-278P-100; rabbit, 1:100, Covance, Princeton, NJ), Tbr2 (http://www.abcam.com/TBR2--Eomes-antibody-EPR19012-ab183991.pdf) (ab183991; rabbit, 1:400, Abcam, Cambridge, United Kingdom), or Ki67 43 (#12202; rabbit, 1:200, Cell Signaling, Danvers MA). Alexa Fluor secondary antibodies (488 and 594) were used at 1:200 concentrations (Thermo Fisher Scientific, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%